6x+3x=4-5(2x-3)

Simple and best practice solution for 6x+3x=4-5(2x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+3x=4-5(2x-3) equation:


Simplifying
6x + 3x = 4 + -5(2x + -3)

Combine like terms: 6x + 3x = 9x
9x = 4 + -5(2x + -3)

Reorder the terms:
9x = 4 + -5(-3 + 2x)
9x = 4 + (-3 * -5 + 2x * -5)
9x = 4 + (15 + -10x)

Combine like terms: 4 + 15 = 19
9x = 19 + -10x

Solving
9x = 19 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
9x + 10x = 19 + -10x + 10x

Combine like terms: 9x + 10x = 19x
19x = 19 + -10x + 10x

Combine like terms: -10x + 10x = 0
19x = 19 + 0
19x = 19

Divide each side by '19'.
x = 1

Simplifying
x = 1

See similar equations:

| x^3-14x-20=0 | | (5x-9)(x+7)=0 | | x+2x+2x-5+25=80 | | 48x^2-4=0 | | 2(3p-x)-(-4+x)= | | 2y+4x=106 | | -1.42(3x-5)= | | 2x+4=21 | | 7coshx+8sinhx=1 | | 9+-5(9+2x)=2+4(-3+1x) | | 9-5(2x-9)=2+4(1x-3) | | 7x+3=27+5 | | 2x-11y=23 | | 56-4x=5x+23 | | 13-9x=44-16x | | 226-7x=38x+16 | | 5-9x=29-16x | | -81-9x=-37-8x | | -63-2x=9-10x | | 115-5x=22x+19 | | 13-10x=33-24x | | 2+9y=14 | | 4k+13=7-2k | | 2x+20=11x-70 | | u^2+7u-2=0 | | -.6666x=.8888 | | 5=(-16)p | | -14x=14 | | b^3+49b=0 | | 5=16p | | (20+p)*3+p= | | 20+p*3= |

Equations solver categories